Rheumatic fever pathogenesis: Approach in research needs change - Rajendra Tandon (Wolters Kluwer Medknow Publications, 2012)
Despite identifying that rheumatic fever (RF) is the result of an immunological reaction following group-A beta-hemolytic streptococcal infection, the pathogenesis remains elusive. RF has been incorrectly designated as causing pancarditis, since it does not cause myocarditis. Research directed toward myocarditis, targeting myosin to unravel the pathogenesis has not succeeded in more than 60 years. RF causes permanent damage to cardiac valves. The mitral valve (MV), derived from the wall of the left ventricle, is composed of a central core of connective tissue, covered on both sides by endothelium. The left ventricle does not have either myocardial or intermyocardial connective tissue involvement in RF. By exclusion, therefore, the primary site of RF damage appears to be the endothelium. Evaluation of the histopathology and immunopathology indicates that RF is a disease of the valvular and vascular endothelium. It is not a connective tissue disorder. Research to identify pathogenesis needs to be focused toward valvular endothelium.